Monitoring of Gamma Radiation Prior to Earthquakes in a Study of Lithosphere-Atmosphere-Ionosphere Coupling in Northern Tien Shan - Nazyf Salikhov; Alexander Shepetov; Galina Pak; Serik Nurakynov; Vladimir Ryabov; Nurzhan Saduyev; Turlan Sadykov; Zhumabek Zhantayev; Valery Zhukov (Atmosphere, 2022)
Monitoring radiation background in the near-surface atmosphere and gamma rays, geoacoustic emission, and temperature in a borehole at 40 m depth, as well as Doppler sounding on a low-inclined radio pass, proceeded at the Tien Shan mountain station (3340 m a.s.l.) in northern Tien Shan with the common goal of searching for seismogenic effects preceding earthquakes. The flux of gamma rays in the borehole varied negligibly between the days, and it was not influenced by precipitation. Characteristic bay-like drops of the gamma ray flux were found (2–8) days before the M5.0–M6.2 earthquakes. In an M4.2 earthquake event with a 5.3 km epicenter distance, anomalies were detected (7–10) days before the earthquake in variation of the gamma ray flux, geoacoustic emission, and temperature. Simultaneously with gamma rays, a disturbance was detected in the Doppler shift of the ionospheric signal. Similarly, ionosphere disturbances triggered by the growth of radioactivity in the near-surface atmosphere were found in a retrospective analysis of the Doppler shift data acquired after underground nuclear explosions at the Semipalatinsk testing site. This effect is considered from the viewpoint of the lithosphere-atmosphere-ionosphere coupling concept.